PERAN PROFITABILITAS MEMEDIASI PENGARUH DIVERSIFIKASI TERHADAP RETURN SAHAM - Dewi, Gusti Ayu Ketut Chandni; Wiagustini, Luh Putu; Sedana, Ida Bagus Panji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The purpose of this study was to assess : (1) diversification effect in profitability, (2) diversification effect to stock return, (3) profitability effect on stock return, (4) diversification effect on stock return through profitability. The population in this research is manufacturing companies listed in Indonesia Stock Exchange. This research used purposive sampling based on companies doing business diversification of 99 companies amount. Based on path analysis method, this research found that diversification have positive and significant  effect on profitability, diversification have positive and significant  effect on stock return, profitability have positive and significant  effect on stock return and profitability is able to mediate the ef          fect of diversification on stock return
Keywords: Diversification, Profitability, Stock Return